ANALISIS DIGITAL MARKETING DALAM UPAYA MENINGKATKAN BRAND AWARENESS UIN SUNAN AMPEL MELALUI PLATFORM INSTAGRAM - Maulida, Alifia Cahya (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
The development of digital technology has transformed communication patterns in higher education institutions in building their image and competitiveness. The us of the instagram platform has become an important medium of information for institutions. This study aims to analyze the implementation of digital marketing strategies through the instagram platform in a effort to enhace the brand awareness of UIN Sunan Ampel Surabaya. This research use a descriptive qualitative method with a case study approach, focusing on UIN Sunan Ampel Surabaya as the object of study. Data were colleted from two primary sources: first, in-depth interviews with the public relations team managing the university’s instagram platform and active students of UIN Sunan Ampel Surabaya, and second, obsevations of the university’s official instagram account. Data analysis was conducted using triangulation techniques to ensure the validity and reability of the findings. The study reveals that: 1) the RRI (Relate, Receh, Informatif) strategy is effective in supporting the success of UIN Sunan Ampel’s digital marketing efforts; 2) active student involvement in content production enhances massage authenticity and emotional connection with the audience and 3) the increase in engagement and information reach has a tangible impact on the annual growth of student enrollment. This study shows that RRI-based digital marketing strategies and active student involvement in conten production can be used as an active model for universities in increasing brand awareness and institutional competitiveness in the digital era.ABSTRAKPerkembangan teknologi digital telah mengubah pola komunikasi lembaga pendidikan tinggi dalam membangun citra dan daya saingannya. Pemanfaatan platform instagram menjadi sarana informasi bagi suatu lembaga. Penelitian ini bertujuan untuk menganalisis penerapan strategi digital marketing melalui platform instagram dalam upaya meningkatkan brand awareness UIN Sunan Ampel Surabaya. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus terhadap UIN Sunan Ampel Surabaya sebagai obyek penelitian. Data dikumpulkan melalui dua sumber yaitu pertama, wawancara mendalam dengan tim humas yang mengelola platform instagram dan mahasiswa aktif UIN Sunan Ampel Surabaya. Kedua, observasi terhadap platform instagram UIN Sunan Ampel Surabaya. Analisis dilakukan dengan teknik triangulasi untuk memastikan validitas dan reliabilitas data. Penelitian ini menghasilkan temuan berupa: 1) Strategi RRI (Relate, Receh, Informatif) efektif sebagai penunjang keberhasilan digital marketing tim humas UIN Sunan Ampel Surabaya; 2) keterlibatan aktif mahasiswa dalam produksi konten meningkatkan keautentikan pesan dan kedekatan emosional dengan audiens dan 3) peningkatan engagement serta jangkauan informasi memiliki dampak nyata terhadap kenaikan jumlah pendaftar setiap tahunnya. Penelitian ini menunjukkan bahwa strategi digital marketing berbasis RRI dan keterlibatan aktif mahasiswa dalam produksi konten dapat dijadikan model aktif bagi perguruan tinggi dalam meningkatkan brand awareness dan daya saing kelembagaan di era digital.